Aflatoxin contamination of dried red chilies: Contrasts between the United States and Nigeria, two markets differing in regulation enforcement. (October 2017) - Singh, Pummi; Cotty, Peter J.
Abstract: Dried red chilies are among the world's most consumed spices. From farm to fork, chilies go through cropping, harvest, drying, processing and storage. Chilies are susceptible to infection by aflatoxin producing fungi and subsequent contamination by aflatoxins at every stage. Aflatoxins are highly regulated, hepatotoxic carcinogens produced by fungi in Aspergillus section Flavi . The current study examined prevalence of aflatoxin B1 (AFB1 ) in chilies from markets across the United States (US) and Nigeria, and determined predisposition of chilies to aflatoxins post-harvest. Aflatoxin B1 was detected in 64% chilies from US markets (n = 169), and 93% of Nigerian chilies (n = 55) with a commercial lateral flow assay (Limit of Detection = 2 μg/kg). Two percent of US samples exceeded the aflatoxin regulatory limit of 20 μg/kg, while the highest concentration detected was 94.9 μg/kg. Aspergillus spp. could be recovered only from 40% of samples from the US, and aflatoxin levels did not correlate with quantities of Aspergillus section Flavi (Colony Forming Units g −1 ), suggesting fungi associated with chilies in US markets were killed during processing. Both average AFB1 concentrations and fungal quantities were significantly higher ( p < 0.01) in Nigerian chilies. The most contaminated sample contained 156 μg/kg AFB1 . Aflatoxin concentrations in Nigerian chilies increased as an exponential function of the quantities of Aspergillus section Flavi ( r 2 = 0.76 ). Results indicate that high rates of chili consumption may be associated with unacceptable aflatoxin exposure. Highlights: Chilies are a source of exposure to the human carcinogen Aflatoxin B1 (AFB1 ). Over 60% of chilies purchased in US and Nigerian markets contained AFB1 . Two percent of US and 7% of Nigerian chilies were unfit for human consumption. Chilies from Nigeria contained more fungi and AFB1 than US chilies. Post-harvest processing influences potential for AFB1 formation.